HUBUNGAN PARITAS, ANEMIA DAN KEKURANGAN ENERGI KRONIK ( KEK ) DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH - Dian Safitri; Hasbiah; Satra Yunola; Tuti Farida (Jurnal Kesehatan dan Pembangunan, 2023)
Low Birth Weight Babies (LBW) is a serious problem faced by the world because it is a cause of morbidity and mortality in the neonatal period. Problems that often arise as complications of LBW are hypoglycemia, hypothermia, hyperbilirubinemia, infection or sepsis and drinking disorders (Reni, 2019). Pregnant women with poor nutritional status or experiencing CED (Chronic Energy Deficiency) tend to give birth to LBW babies and are faced with a greater risk of death than babies born to mothers with normal weight. The research method uses an analytical survey with a cross sectional approach. The population of this study were all mothers who gave birth in the working area of ​​the Talang Pangeran Health Center totaling 323 mothers. The sampling technique was accidental sampling with a sample size of 76 respondents. Data analysis used univariate analysis and bivariate analysis. The results of the study showed that there was a relationship between parity (p value = 0.018), anemia (p value = 0.014) and chronic energy deficiency (KEK) (p value = 0.025) with the incidence of low birth weight in the Talang Pangeran Health Center Work Area in 2020.